Actividad Antibacteriana y Citotoxicidad de Cinco Especies Vegetales de la Zona Altoandina y Amazónica de la Región del Cusco - Cardona Rivero, Anahi Karina (2022)
The objective of this research was to evaluate the antibacterial activity and cytotoxicity of five plant species from the high Andean and Amazonian zones of the Cusco region. A descriptive, non-experimental and transversal research was developed. Preliminary studies were also conducted consisting of qualitative phytochemical screening and UV-Vis spectrophotometric analysis of the species Acicarpha tribuloides Jussieu (Estrella Kisca), Gamochaeta spicata (Queto-Queto), Minthostachys glabrescens (Bentham) Epling (Muña), Muehlenbeckia volcanica (Bentham) Endlicher (Mullaca) and Piper elongatum M. Vahl (Matico). The samples were collected in different provinces and districts of the Cusco region. Taxonomic identification was carried out in the Vargas CUZ Herbarium of the Universidad Nacional de San Antonio Abad del Cusco. The ethanolic extracts of the five species were obtained by the maceration method; in addition, the essential oil of Muña leaves was prepared by steam distillation. Qualitative phytochemical screening of the extracts was carried out by staining and precipitation reactions. Also, Uv-vis spectrophotometric analysis of the extracts was performed. In the case of antibacterial activity, the minimum inhibitory concentration (MIC) was determined using the macro dilution method in liquid medium and ATCC strains of Escherichia coli 25922, Staphylococcus aureus 29213, Streptococcus pneumoniae 49619 and Salmonella typhimurium 14028. Likewise, the Artemia salina assay was used to determine the degree of toxicity of the extracts. The results obtained in the qualitative phytochemical and UV-Vis spectrophotometric analysis show that the plants investigated contain phenolic compounds, flavonoids, tannins and saponins in higher amounts. On the other hand, with respect to antibacterial activity, Queto-Queto and Mullaca have an effect against Staphylococcus aureus, Escherichia coli and Streptococcus pneumoniae, while Matico acts against Streptococcus pneumoniae and Staphylococcus aureus. In the case of the Estrella Kisca and Muña, they were positive against Salmonella typhimurium and Escherichia coli. The cytotoxicity test with Artemia salina showed that the extracts of Estrella Kisca and Queto - Queto are very toxic with a LC50 of 19,639 and 58,104 respectively. On the other hand, the extracts considered moderately toxic are those of Muña, Mullaca and Matico with LC50 of 100,092, 415,451 and 158,006 respectively.